Hypothermia amplifies somatosensory evoked potentials in uninjured rats - Madhok, Jai (2012)
Temperature fluctuations significantly impact neurologic injuries in intensive care units. As benefits of therapeutic hypothermia continue to unfold, many of these discoveries are generated by studies in animal models undergoing experimental procedures under the influence of anesthetics. We studied the effect of induced hypothermia on neural electrophysiological signals of an uninjured brain in a rodent model while under isoflurane. Fourteen rats were divided into two groups (n=7 each), based on electrode placement, at either frontal-occipital (FO) or primary somatosensory (SS) cortical locations. Neural signals were recorded during normothermia (T = 36.5–37.5°C), mild hypothermia (T = 32–34°C) and hyperthermia (T = 38.5–39.5°C). Burst-suppression ratio (BSR) was used to evaluate EEGs, and amplitude-latency analysis was used to assess SSEPs. Hypothermia was characterized by an increased BSR (Mean+STD) of 0.58±0.06 in hypothermia versus 0.16±0.13 in normothermia, p<0.001 in FO; and 0.30±0.13 in hypothermia versus 0.04±0.04 in normothermia, p=0.006 in SS. There was potentiation of SSEP (2.89 ±1.24 times normothermic baseline in hypothermia, p=0.02) and prolonged peak latency (N10: 10.8±0.4 msec in hypothermia versus 9.1±0.3 msec in normothermia; P15: 16.2±0.8 msec in hypothermia versus 13.7±0.6 msec in normothermia; p<0.001), whereas hyperthermia was primarily marked by shorter peak latencies (N10: 8.6±0.2msec, P15: 12.6±0.4 msec; p<0.001). In the absence of brain injury in a rodent model, hypothermia induces significant increase to the SSEP amplitude while increasing SSEP latency. Hypothermia also suppressed EEGs at different regions of the brain by different degrees. The changes to SSEP and EEG are both reversible with subsequent rewarming.